Programming Using Aspects - Saxena, Saurabh; Kumar , Meena (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
We can define an Aspect oriented programming as eecuting the code wheneer a program shows certain behaviors. Aspects are an additional unit of modularity. Aspects can be reused. By reducing code tangling it makes it easier to understand what the core functionalit of a module is. An “aspect weaer” takes the aspects and the core modules and composes the final system.